PENGARUH PEMBERIAN SARI KURMA PADA REMAJA PUTRI DENGAN ANEMIA DEFISIENSI ZAT BESI DI PALANGKA RAYA - Yulia Kriska Damiri; Yuniarti Yuniarti (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2020)
The incidence of anemia is a problem most often found in adolescents. Adolescent girls are one group that is prone to suffer from anemia. This is because adolescent girls experience menstruation every month, and are in their infancy and need more iron intake. Dates have many benefits, including preventing anemia, because they are rich in calcium and iron, which are two elective elements that are important for the formation of blood and bone marrow. This study aims to identify the effect of date palm essence on adolescent girls with iron deficiency anemia. The method used is pre-experimental, one group pre-post test design. The sampling technique was porvusive sampling, as many as 34 samples of adolescent girls with the independent variable date palm essence, the dependent variable was iron deficiency anemia. Univariate analysis uses distribution, frequency and presentation. Bivariate analysis, using the Wilcoxon signed rank test.The results of the Wilcoxon signed rank test, Wilcoxon test results signed the rank test, showed there were differences in date palm essence on increasing hemoglobin levels in young women in the Polytechnic of Palangka Raya with a p-value of 0,000 (<0.005). Date palm essence as one solution to increase hemoglobin levels inadolescent girls. Keywords: anemia, hemoglobin, adolescent girls, date palm essence.